Measuring depression in Primary Health Care in Spain: Psychometric properties and diagnostic accuracy of HSCL-5 and HSCL-10 - Rodríguez-Barragán, María; Fernández-San-Martín, María Isabel; Clavería, Ana; Le Reste, Jean Yves; Nabbe, Patrice; Motrico, Emma; Gómez-Gómez, Irene; Peguero-Rodríguez, Eva (Frontiers in Medicine, 2023)
Background Depression has a high prevalence among European countries. Several instruments have been designed to assess its symptoms in different populations. The Hopkins Symptom Checklist 25 (HSCL-25) scale has been identified as valid, reproducible, effective, and easy to use. There are short versions of this scale that could be useful in Primary Care (PC) settings, but their psychometric properties are unknown. Aim To assess in PC patients the psychometric properties and diagnostic accuracy of the Spanish version of the HSCL-10 and the HSCL-5 consisting of 10 and 5 items, respectively. Methods A multicenter, cross-sectional study was carried out at six PC centers in Spain. The HSCL-25 was administered to outpatients aged 45–75 who also participated in the structured Composite International Diagnostic Interview (CIDI). HSCL-10 and HSCL-5 were assessed and compared to HSCL-25 regarding total score correlation, internal consistency, and criterion validity against the gold-standard CIDI. This is a methodological study from a secondary data analysis and the primary data has been previously published. Results Out of 790 patients, 767 completed the HSCL-25 and 736 the CIDI interview (96.0%). Cronbach’s Alpha was 0.84 for HSCL-10 and 0.77 for HSCL-5. The known-group method and confirmatory factor analysis were acceptable for the establishment of construct validity. Sensitivity was 79.7% (CI95%, 67.7–88.0%) for HSCL-10, and 78.0% (CI95%, 65.9–86.6%) for HSCL-5, whereas specificity was 83% (CI95%, 80.0–85.7%) for HSCL-10, and 72.8% (CI95%, 69.3–76.0%) for HSCL-5. Area under the curve against CIDI was 0.88 (CI95%, 0.84–0.92%) for HSCL-10, and 0.85 (CI95%, 0.81–0.89%) for HSCL-5. Optimum cutoff point calculated with Youden Index was 1.90 for the HSCL-10 and 1.80 for the HSCL-5. Conclusion HSCL-10 and HSCL-5 are reliable and valid tools to detect depression symptoms and can be used in PC settings.